1979
DOI: 10.1002/pol.1979.130170706
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of anionic oligomerization of vinyl monomers. VI. Low‐molecular‐weight stereoregular polymers of 2‐vinylpyridine prepared with li salts as initiators in THF

Abstract: We have recently shown that oligomers [7] and [8] of 2-vinylpyridine prepared with Li and Na salts as initiators in THF [eq. (l)] are predominantly Q 95%) isotactic (1,2). -- C2I-C61C7I-C121 C21. C71 n=l; 131. CSI ~2 ; 141.C91 n=3; C51. [lo] 11.5-6; [6]. [ I 1 1 n=6-12 1123 n -Thus, the methylation of and the 2-vinylpyridine addition to anion [2] occurs with the same meso stereochemistry. Moreover, with a 4-pyridyl unit in ultimate position or both ultimate and penultimate positions the methylation of such an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The observation that the addition of 2-vinylpyridine in THF at low temperature in the presence of Li ions is not stereoregular resolves some previously unexplained findings. 14 Thus termination with 13C-labeled CH3I of a low molecular weight (DP 60) "living" polymers prepared in THF in the presence of Li+ produced a polymer showing a distinct 13CH3 doublet absorption, the origin of which was unclear. The present results clearly point to the two absorptions as being due to the (rm) and (mm) groups of stereoisomers.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the addition of 2-vinylpyridine in THF at low temperature in the presence of Li ions is not stereoregular resolves some previously unexplained findings. 14 Thus termination with 13C-labeled CH3I of a low molecular weight (DP 60) "living" polymers prepared in THF in the presence of Li+ produced a polymer showing a distinct 13CH3 doublet absorption, the origin of which was unclear. The present results clearly point to the two absorptions as being due to the (rm) and (mm) groups of stereoisomers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some hints on the occurrence of side reactions during the anionic polymerization of 2VPy were obtained from NMR spectra of the polymers. Hogen-Esch and Tien supposed that broadening of NMR signals, which could also be observed from P2VPy spectra shown by Natta et a1.l') as well as by Matsuzake and Sugimoto"), was rather due to by-products than to poor stereoregularity of the polymers 13). These authors reported also that they isolated byproducts formed during anionic oligomerization and supposed that the isolation of byproducts from polymerization would be considerably more difficult 13).…”
Section: Introductionmentioning
confidence: 89%
“…90MHz 13 C NMR Spectra Figure 4 shows 90 MHz aromatic carbon resonance spectra of the various poly(2-vinylpyridine) samples in CH30D solution. All five aromatic carbons are observed in separate regions and all show sensitivity to stereosequence distribution effects.…”
Section: H Nmr Spectramentioning
confidence: 99%
“…20MHz 13 C NMR Spectra 13 C NMR spectra of the epimerized polymers in CD30D solution at 40° were initially studied with a 20 MHz spectrometer. In all previous reports, the resonance of the quaternary aromatic carbons (C-2) is claimed to be the one most sensitive to tacticity.…”
Section: H Nmr Spectramentioning
confidence: 99%
See 1 more Smart Citation